A Comparison of 18F-FDG-PET/MRI and 18F-FDG-PET/CT in the Cancer Staging of Locoregional Lymph Nodes - Slouka, David; Krcal, Jiri; Kostlivy, Tomas; Hrabacka, Petr; Skalova, Alena; Mirka, Hynek; Topolcan, Ondrej; Kucera, Radek (In Vivo, 2020)
AIM: The aim of the study was to evaluate the yields of 2-deoxy-2-[18F]-fluoro-D-glucose positron-emission tomography/magnetic resonance imaging (18F-FDG-PET/MRI) and 18F-FDG-PET/computed tomography (CT) for the detection of metastatic involvement of locoregional neck nodes in patients with head and neck malignancy. PATIENTS AND METHODS: A total of 90 patients (66 men and 24 women) met the inclusion criteria. Preoperative staging was performed: 53 examinations using PET/CT and 37 using PET/MRI. RESULTS: For PET/MRI, the study demonstrated a sensitivity of 89%, specificity of 64%, positive predictive value of 85%, and negative predictive value of 70%; PET/CT had a sensitivity of 95%, specificity 47%, positive predictive value of 82%, and negative predictive value of 78%. CONCLUSION: Both methods have a high yield in N-clinical staging with statistically insignificant differences. We assume PET/MRI to be the first-choice method in organ-targeted examinations, for pediatric patients and repeat examinations. In cases of MRI contraindication, PET/CT can be used with no impact on the quality of care.
Keywords: Magnetic Resonance Imaging; Female; dítě; Positron Emission Tomography Computed Tomography; Lymphatic Metastasis; lymfatické metastázy; ženské pohlaví; Tomography, X-Ray Computed; radiofarmaka; fluorodeoxyglukosa F18; lymfatické uzliny; lidé; staging nádorů; PET/CT; magnetická rezonanční tomografie; Sensitivity and Specificity; senzitivita a specificita; Male; Radiopharmaceuticals; Lymph Nodes; počítačová rentgenová tomografie; pozitronová emisní tomografie; Child; Fluorodeoxyglucose F18; mužské pohlaví; Neoplasm Staging; Positron-Emission Tomography; Humans